AGAMA DAN PERILAKU BISNIS STUDI KOMPARASI TENTANG MAKNA ETIKA BISNIS BAGI PELAKU SEKTOR INFORMAL KALANGAN ETNIS MADURA DAN MINANGKABAU DI KOTA MALANG - Muhammad Djakfar (El-QUDWAH, 2006)
Religion, in this case Islam is the main motivation in constructing ethos of work and directing business behavior of businessmen. In Indonesia, Madura and Minangkabau ethnic are known as obedient Moslem, hard workers, tough and zealous businessmen who do business in informal sector. So far, the business behavior of both ethnics is not really well-known, therefore we conduct the research to know more about their business behavior viewed from the perspective of ethics in Malang. There are two aspects studied in this research. First, is the meaning of business ethic according to both ethnics, and second, is the implementation in the relationship between businessmen, the service to the consumer, and their attitude toward environment. The data are taken through thorough interview, involved observation, and documentation, and then studied using phenomenological method and analyzed with three phases as Miles and Hubermas states, they are data reduction, data display, and conclusion drawing/verification. The research shows that both ethnics give the same meaning to the ethic of business. To them, business is a part  of religious service so that to get good wealth they have to give priority to the value of ethics. Both ethnics believe that that competition is a usual thing in business, all sides are required to obey the value of ethics. They try to be fair and transparent to the consumers, also, they care their environment because they have social responsibility as the compensation to the society that has become their consumers.Kata kunci : Agama, Perilaku Bisnis, Makna Etika Bisnis, Sektor Informal, Etnis Madura, Etnis Minangkabau